2004
DOI: 10.1021/ja031906i
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Proton Catalysis:  A Catalytic Enantioselective Direct Aza-Henry Reaction

Abstract: Despite Nature's longstanding ability to use a proton, the most prevalent Lewis acid, to both activate and orient a substrate during an enantioselective reaction, this work represents the first example of this phenomenon outside of a protein. A chiral, nonracemic BisAMidine (BAM) ligand was designed, synthesized, and complexed to the proton of a Brønsted acid. The resulting coordination compound catalyzed the production of enantioenriched product from the combination of a Schiff base and nitroalkane (the aza-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(116 citation statements)
references
References 28 publications
(18 reference statements)
1
109
0
4
Order By: Relevance
“…Then itro derivative 188 is obtained as a1 :1 mixture of diastereomersb ya n enantioselective nitro-Mannichr eaction between the corresponding N-acylimine and bromonitromethane. [138] Thef inalt ripeptide 190 is formed as as ingle diastereomer in good yield.…”
Section: Scheme64 Synthesis Of Chiral Lactone 184mentioning
confidence: 99%
“…Then itro derivative 188 is obtained as a1 :1 mixture of diastereomersb ya n enantioselective nitro-Mannichr eaction between the corresponding N-acylimine and bromonitromethane. [138] Thef inalt ripeptide 190 is formed as as ingle diastereomer in good yield.…”
Section: Scheme64 Synthesis Of Chiral Lactone 184mentioning
confidence: 99%
“…[55] Johnston et al reported the aza-Henry reaction by means of an ammonium salt 19, derived from cyclohexane diamine and quinoline. [56] b-Nitroamines were obtained with high diastereoselectivity and enantioselectivity (Scheme 32). They measured the pK a value of the ammonium salt by Perrin titration method and estimated it to be 5.78, [57] which indicates that the ammonium salt is not strong enough to protonate the imine.…”
Section: Binol Derivativesmentioning
confidence: 99%
“…24 h, cooled, and more LiAlH 4 (0.43 g, 11.3 mmol) was added. The mixture was refluxed for another 24 h. The product was then hydrolysed as described for amine 10 and it was purified by preparative chromatography on neutral alumina (8 (14).…”
Section: (2r3r5s6s)-(56-dimethoxy-56-dimethyl-14-dioxane-23-dimentioning
confidence: 99%
“…The vast majority of these reactions are amine-based [10a], proceeding either via the formation of an enamine or imonium ions. The use of chiral Brønsted bases, inactive on their own but activated by addition of an acid, is another area where there are already a few exciting developments [11] with protonated diamine-type catalysts, such as in the asymmetric direct aldol reaction [12], in the Michael addition of aldehydes or ketones to β-nitrostyrene [13], in aza-Henry reactions [14] and others.…”
Section: Introductionmentioning
confidence: 99%